Microstructural evolution and final properties of a cold-swaged multifunctional Ti-Nb-Ta-Zr-O alloy produced by a powder metallurgy route - Guo, W.; Quadir, Md Zakaria; Moricca, S.; Eddows, T.; Ferry, M. (Elsevier S.A., 2013)
Body centred cubic (BCC) ß-phase multifunctional titanium alloys have been developed with a very unique combination of thermal and mechanical properties. In this investigation, a very low porosity Ti-36.8-Nb-2.7Zr-2.0Ta-0.44O (wt%) alloy was produced by powder sintering, hot forging, solution treatment and cold swaging. X-ray diffraction and transmission electron microscopy (TEM) of the solution treated alloy revealed the presence of a small amount of ?-phase in a predominantly BCC ß-phase matrix. Electron backscatter diffraction (EBSD) of the swaged alloy revealed a highly elongated and fragmented microstructure, and a strong <110> fibre texture. TEM also revealed the existence of stress-induced twin lamella, dislocations and ?-phase. Consistent with previous studies on these types of alloys, the swaged alloy exhibited non-linear elasticity during tensile straining, low elastic modulus (45.4GPa), high elastic limit (2.3%), high elongation to failure (8.1%), and a high yield strength (880MPa) and tensile strength (940MPa). The coefficient of thermal expansion was also low (~5×10-6K-1 between 50 and 300°C) in this alloy. © 2013 Elsevier B.V.